Transcending disadvantage: life-histories of learners at a township school in South Africa - Ntete, Susan (University of the Western Cape, 2014)
Philosophiae Doctor - PhD === This is a study of the discourses of empowerment and disempowerment that emerge from the critical discourse analysis (CDA) of life-histories written by two classes of Grade 11 high school learners in a township school in Cape Town, South Africa. The line of argument presented by this thesis is that there are political, socio-economic, familial and institutional factors and the discourses that construct them which affect learners’ resilience. === South Africa